The importance of preliminaries items - Abdul Ghani, Norhisham (2006)
The items found in the preliminaries section of a bill of quantities are usually the most difficult to price and would produce the greatest variation in prices with each contractor having his own idea of pricing preliminaries. Not all preliminary items need to be priced, some are remain unpriced. The aim of the study to understand the preliminaries item and identify mandatory items in selected project that should be priced by contractors. The findings will give benefits to contractor as strategies to price preliminaries accordingly and accurately. The study conducted with reference to the selected group of contractor who has vast experiences in tender pricing. The methodology adopted for the study includes interviews with contractor and industry wide questionnaire survey among the contractors that involved in JKR projects. The data collected were analysed using content analysis method and using appropriate statistical method such as frequency analysis and relative index method. The study has determined what the items are considered as mandatory items that should be price by contractor and the strategies in pricing preliminaries as a guide. Apart from that the study also established factors that influence in pricing preliminaries as well as can help contractor pricing preliminary accurately